Green RP-HPLC method for simultaneous quantification of epigallocatechin-3-gallate and rosmarinic acid in lipid-based nanocarriers and biological fluids: Quality by design-driven optimization and lean six sigma approach - Rahul Koli; V.S. Mannur (Green Analytical Chemistry)
This study presents the development and validation of a reverse-phase high-performance liquid chromatography (RP-HPLC) method for concurrent quantification of EGCG and RA in prepared lipid-based nanocarriers and biological fluids using a QbD approach, greenness assessment, and Six-Sigma methodology. Initially, variations in critical analytical attributes were identified using the Ishikawa fishbone diagram and Risk Priority Number scores. A Taguchi Orthogonal Array design was employed to screen the critical method parameters influencing method development. Systematic optimization of the RP-HPLC method was subsequently achieved using a Box-Behnken design, with the % organic phase, flow rate, and column temperature as the variables. The responses were retention time, tailing factor, and theoretical plates for both EGCG and RA. Chromatographic separation was accomplished with a methanol and 0.1% formic acid (60:40) isocratic flow system on a Phenomenex Luna C18 column (4.6 × 250 mm, 5 μm) at a 1 mL/min flow rate. The method was rigorously validated according to ICH guidelines. Linearity was observed over a concentration range of 2 to 10 µg/mL for both EGCG and RA, yielding correlation coefficients of 0.998 and 0.999, respectively. The LOD and LOQ were determined to be 0.51 µg/mL and 1.54 µg/mL for EGCG, and 0.35 µg/mL and 1.07 µg/mL for RA. Moreover, the %RSD for all validation parameters were consistently below 2%. Forced degradation studies were conducted under acidic, basic, oxidative, and photolytic conditions to elucidate potential degradation pathways and identify degradation products. The developed method was applied to estimate EGCG and RA in prepared lipid-based nanocarriers and biological fluids like blood plasma and urine. Recovery assays in lipid-based nanocarriers, plasma, and urine samples demonstrated excellent recoveries (96.2–102.1%). The method's greenness was assessed using various tools, and its accuracy was evaluated using Six Sigma methodology. Overall, the developed HPLC method offers a rapid, sensitive, and reliable approach for quantifying EGCG and RA, laying the groundwork for their further investigation as anticancer agents, alone and in combination therapies.